Review of the Frequent Occurrence of Pterygium on the Nasal Side - Mingzhi Lu; He Ren; Xiaoxi Deng; Kuiliang Yang; Han Zhang; Wanju Yang; Hong Zhang; Yiqiao Xing (Journal of Current Ophthalmology, 2024)
Purpose: To investigate the predominant occurrence of pterygium on the nasal side of the eye and elucidate the underlying mechanisms. Methods: A comprehensive review was conducted by searching the PubMed and Google Scholar databases for articles published from January 1990 to May 2023. Keywords used included “pterygium”, “nasal side”, “risk factors”, “pathogenesis”, and “review”. Articles were selected based on their relevance to the pathogenesis of pterygium. Results: This review identifies multiple factors that may contribute to the frequent occurrence of pterygium on the nasal side. These include increased exposure to ultraviolet light, genetic predispositions, tear film abnormalities, viral infections, allergic reactions, and habitual eye rubbing. Conclusions: Comparing responses of the nasal and temporal conjunctiva to various physical and chemical stimuli could provide insight into the mechanisms driving this condition.